An evaluation model for an effective risk assessment in the rent to buy property market. Issue 1 (2nd December 2019) - Tajani, Francesco; Morano, Pierluigi; Salvo, Francesca; De Ruggiero, Manuela
Abstract : Purpose: In this research a model for the rationalization of the assessment in a rent to buy contract has been proposed, in order to contextualize the economic amounts involved in the negotiation according to the specific market risk of the area where the property is located. The paper aims to discuss this issue. Design/methodology/approach: The model borrows the logical principles of operational research, in order to take into account the convenience constraints of the parties involved (seller and buyer) and to determine the minimum amount of the additional annual rent to be charged as down payment on the final sale price, compensating the investment risk. The procedure proposed for the risk assessment combines the discrete modeling of real option analysis and the exponentially weighted moving average method, in order to weigh appropriately the data available for the specific area in the analysis. Findings: Considering the limit conditions of variability of the property market value at the time provided for the notarial deed, the proposed model returns two values (minimum and maximum) for a fixed contract duration and for a specific market area for the annual additional rent, which define the reference range to ensure the compliance with the convenience constraints of the parties involved. Practical implications: In order to test the reliability of the developed methodology, the model has been implemented to the 24 "microzones" defined by the Italian Revenue Agency for the city of Bari (Southern Italy). The results obtained were then georeferenced, in order to create thematic maps of convenience for the subjects interested in the rent to buy formula. The developed maps define a useful support to be consulted in the negotiation phase between the seller and the buyer, allowing both to verify the investment conveniences within the limits of their disposable incomes and their needs. Originality/value: The tabulated values of the down-payment amounts and the related thematic maps constitute a valid support for both the parties in the initial negotiation phase of the contractual conditions: in fact, if comparable data for the assessment of the market value and the market rent at the time of the stipulation of the contract are ordinarily available, the increase in the rent, to be charged as the annual down payment on the final purchase price, is generally entrusted to the contractual capabilities of the subjects involved, since there is no market reference that can direct an appropriate assessment.